Decreased phosphatidylcholine plasmalogens – A putative novel lipid signature in patients with stable coronary artery disease and acute myocardial infarction. (March 2016) - Sutter, Iryna; Klingenberg, Roland; Othman, Alaa; Rohrer, Lucia; Landmesser, Ulf; Heg, Dierik; Rodondi, Nicolas; Mach, Francois; Windecker, Stephan; Matter, Christian M.; Lüscher, Thomas F.; von Eckardstein, Arnold; et al.
Abstract: Objective: Glycerophospholipids and sphingolipids are structurally heterogeneous due to differences in the O- and N-linked fatty acids and head groups. Sphingolipids also show a heterogeneity in their sphingoid base composition which up to now has been little appreciated. The aim of this study was to investigate the association of certain glycerophospholipid and sphingolipid species with stable coronary artery disease (CAD) and acute myocardial infarction (AMI). Methods: The lipid profile in plasma from patients with stable CAD (n = 18) or AMI (n = 17) was compared to healthy subjects (n = 14). Sixty five glycerophospholipid and sphingolipid species were quantified by LC-MS. The relative distribution of these lipids into lipoprotein fractions was analyzed. Results: In the CAD cohort, 45 glycerophospholipid and sphingolipid species were significantly lower compared to healthy controls. In the AMI group, 42 glycerophospholipid and sphingolipid species were reduced. Four PC plasmalogens (PC33:1, PC33:2, PC33:3 and PC35:3) showed the most significant difference. Out of eleven analyzed sphingoid bases, four were lower in the CAD and six in the AMI group. Sphingosine-1-phosphate (S1P) levels were reduced in the AMI group whereas an atypical C16:1 S1P was lower in both groups. Phosphatidylcholine and sphingomyelin species were exclusively present in lipoprotein particles, whereas lysophosphatidylcholines were mainly found in the lipoprotein-free fraction. The observed differences were not explained by the use of statins as confirmed in a second, independent cohort. Conclusions: Reduced levels of four PC plasmalogens (PC33:1, PC33:2, PC33:3 and PC35:3) were identified as a putatively novel lipid signature for CAD and AMI. Highlights: Sixty five plasma glycerophospho- and sphingolipid species were quantified in patients with stable CAD or AMI and compared to healthy subjects. 45 and 42 glycerophospholipid and sphingolipid species were significantly lower in the CAD and AMI group, respectively. Four PC plasmalogens (PC33:1, PC33:2, PC33:3 and PC35:3) showed the most significant difference and were associated with HDL. The observed differences were not explained by the use of statins as confirmed in a second, independent cohort.